2011
DOI: 10.1590/s1413-86702011000600008
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic bead technology for viral RNA extraction from serum in blood bank screening

Abstract: The manual magnetic bead-based extraction in combination with real-time PCR detection can be used to routinely screen blood donation for viremic donors to further increase the safety of blood products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In the last decade, several studies have demonstrated the use of magnetic beads to extract nucleic acids from a variety of matrices, including serum (Sun et al, 2014), urine (Shan et al, 2012), sputum (He et al, 2017), whole blood (Albertoni et al, 2011), tissue (Mathot et al, 2011), and wastewater (La Rosa et al, 2010; Yuan et al, 2019). While conventional approaches involve both pre-concentration and extraction using magnetic beads, an emerging methodology involves direct extraction using magnetic beads in the absence of a pre-concentration step.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, several studies have demonstrated the use of magnetic beads to extract nucleic acids from a variety of matrices, including serum (Sun et al, 2014), urine (Shan et al, 2012), sputum (He et al, 2017), whole blood (Albertoni et al, 2011), tissue (Mathot et al, 2011), and wastewater (La Rosa et al, 2010; Yuan et al, 2019). While conventional approaches involve both pre-concentration and extraction using magnetic beads, an emerging methodology involves direct extraction using magnetic beads in the absence of a pre-concentration step.…”
Section: Introductionmentioning
confidence: 99%